2016
DOI: 10.1093/annonc/mdw287
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of axitinib (AG-013736) in patients with incurable adenoid cystic carcinoma

Abstract: Although the primary end point was not met, axitinib exhibited clinical activity with tumor shrinkage achieved in the majority of patients with progressive disease before trial enrollment. Analysis of MYB biomarkers and genomic profiling suggests the hypothesis that 4q12 amplified ACCs are a disease subset that benefit from TKI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 22 publications
5
79
1
2
Order By: Relevance
“…12 Moreover, an ORR of 9% was reported by Alan Ho in a phase II study including only patients with ACC. 15 In patients with ACC, a comparable activity was observed with chemotherapy (ORR, 5%-15%) 18 with a median OS ranging from 14 to 19 months with single agent to 8 to 67 months with polychemotherapy 18,19 ). On the contrary, in non-ACC histotypes, chemotherapy seems to be more active (ORR, 20%-40%) than antiangiogenic agents 19 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…12 Moreover, an ORR of 9% was reported by Alan Ho in a phase II study including only patients with ACC. 15 In patients with ACC, a comparable activity was observed with chemotherapy (ORR, 5%-15%) 18 with a median OS ranging from 14 to 19 months with single agent to 8 to 67 months with polychemotherapy 18,19 ). On the contrary, in non-ACC histotypes, chemotherapy seems to be more active (ORR, 20%-40%) than antiangiogenic agents 19 ).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, preclinical data showed that vascular endothelial growth factor receptor (VEGFR) pathway is frequently upregulated in SGCs, [7][8][9] and VEGF expression correlated with worse prognosis. 15 Our aim was to assess the activity of axitinib in patients with SGCs including mainly patients with non-ACC. 12,13 Axitinib is a second-generation antiangiogenic drug, more potent than sorafenib in inhibition of VEGFR-2 (IC 50 nmol/L VEGFR2 inhibition 0.2 vs 90, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD duration (SDD) has been described in several trials for patients with ACC [2531]. It is unclear if SD represents a marker of drug activity or simply the indolent behavior of this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Because OHSV G47∆-IL12 does not only induce anti-tumor immunity but also produce anti-angiogenic activities [30], it is hypothesized that anti-tumor effects of G47∆-IL12 treatment would synergize with anti-vascular drugs. Axitinib (AG-013736) is an FDA approved, orally administered potent small molecule tyrosine kinase inhibitor (TKI), which inhibits VEGF receptor (VEGFR) 1-3, platelet-derived growth factor receptor beta (PDGFR-β) and receptor tyrosine kinase c-KIT (CD117) [115], and shows promising anti-vascular and anti-tumor activity in a variety of advanced stage cancers, including GBM [116][117][118]. In addition to anti-vascular effects, it also induces anti-tumor immune effects [119,120].…”
Section: Inhibition Of Tumor Angiogenesis Enhances Anti-tumor Potentimentioning
confidence: 99%